VD_FINDINFO Décision / 2014 / 314 vom 14. März 2013 - VD Tribunal cantonal (2013)
CONFLIT D'INTÉRÊTS, AVOCAT, LOI FÉDÉRALE SUR LA LIBRE CIRCULATION DES AVOCATS | 12 LLCA, 127 CPP (CH), 393 al. 1 let. a CPP (CH)